Introduction Of The Basic Concept Of Good Manufacturing Process On Small Medium Enterprises Of Cassava-Based Crackers - Indah Hartati; Darmanto; Laeli Kurniasari; Mochamad Subchan Mauludin; Ernawati Budi Astuti (Fakultas Teknik Universitas Wahid Hasyim, 2025)
One approach to enhance competitiveness among SMEs is through the implementation of Good Manufacturing Practices (GMP). However, the SMEs Slondok Puyur, which produce cassava-based crackers, currently has limited understanding and knowledge regarding the fundamental concepts of GMP. As a result, this community service initiative is designed to introduce the basic principles of Good Manufacturing Processes to the SMEs of Slondok Puyur. The community engagement involved a series of activities that included identifying the steps in the production process, followed by an introduction to the basic concepts of GMP and the exploration of potential applications of GMP within the SMEs of Slondok Puyur. The community engagement successfully informed the SMEs about the definition, aspects, and implementation steps of GMP, as well as the importance of GMP in the growth of SMEs. The community engagement activity also succeeded in identifying potential applications of GMP within the production processes of the cassava-based crackers at the SMEs located in Slondok Puyur.